Factors Associated With Parents' Perceptions of Their Infants' Oral Health Care - Jeanette M. Daly RN, PhD; Steven M. Levy DDS, MPH; Yinghui Xu MS; Richard D. Jackson DMD; George J. Eckert MAS; Barcey T. Levy PhD, MD; Margherita Fontana DDS, PhD (SAGE Publishing, 2016)
Introduction: Parents have an important role ensuring their infants receive oral and medical health care. Their decisions affect the well-being of their children. Methods: This study used data collected from a longitudinal, prospective study with the aim of developing and validating a caries risk assessment tool. The objectives of this study are to ( a ) compare parents' perceptions of how well they do in taking care of the infants' teeth and/or gums versus how well they do in taking care of the infants' medical health and ( b ) determine factors associated with parental perceptions of how well they do in taking care of the infants' teeth and/or gums. Results: A total of 1323 parent/infant pairs were enrolled in the study at Duke University, Indiana University, and the University of Iowa. Through a survey, 283 (21%) of the parents perceived they did an excellent job of both taking care of both the infant's oral and medical health, while 861 (65%) perceived the care of their infant's medical health was better than their care of the teeth and/or gums. In the multivariable model, parents who perceived they provided excellent/very good/good care for the infants' teeth and/or gums were more likely to brush the infant's teeth daily, use toothpaste daily, clean inside the infant's mouth and/or gums daily, and not let the infant have something other than water after brushing and prior to bedtime. Also, those with infants having Medicaid or State Insurance, parents not eating sugary snacks frequently, and parents getting dental checkups at least annually were likely to perceive that they provided excellent/very good/good care for their infant's teeth and/or gums. Conclusions: Parents who provide good infant oral health care are more likely to perceive they provide good care and more likely to have better personal dental health behaviors. This agrees with previous studies concerning older children.